Analisis Pengaruh UMKM (Usaha Mikro Kecil Dan Menengah) Mendapatkan Kredit Usaha Rakyat (KUR) dari Lembaga Keuangan di Kabupaten Bireuen - Jamaluddin, Jamaluddin; Sudarmiatin, Sudarmiatin; Rahayu, Wening Patmi (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The purpose of this study was to analyze the effect of the distribution of People's Business Credit (KUR) by financial institutions on the growth of Micro, Small, and Medium Enterprises (MSMEs) in Bireuen Regency, with a focus on the contribution of KUR in increasing access to financing, competitiveness, and capacity of MSME businesses. This research method uses quantitative data obtained from the results of the questionnaire in the form of age, gender, education level, type of business, and amount of credit given. The population used in this study includes data on the number of customers who received KUR from 2020-2022 with a sample size of 97 respondents. The results of the study showed that the influence of the role of People's Business Credit (KUR) on the growth of Micro, Small, and Medium Enterprises (MSMEs) showed a t-count result of 7.673, which was statistically significantly higher than the t-table value of 1.661 with a very low level of significance, namely 0.000, which is far below 0.05 (5%). The results of the determination coefficient test showed that the R square achieved was 0.678. This indicates that almost half, or around 67.8%, of the variation in the growth of Micro, Small, and Medium Enterprises (MSMEs) can be explained by the distribution of People's Business Credit (KUR). On the other hand, around 32.2% of the remainder is influenced by other variables not examined in this study. The expected impact of this study is to provide a deeper understanding of the effectiveness of KUR in supporting the development of MSMEs, as well as being a reference for policy makers and financial institutions in designing more effective strategies to encourage the growth of the MSME sector, while accelerating poverty alleviation and improving the economic welfare of the community.